KADAR VITAMIN C PADA MANGGA ARUM MANIS YANG DISIMPAN PADA SUHU YANG BERBEDA - Hapsari, Anisa Prima Vera; Hasdar, Muhamad; Daryono, Daryono; Purwanti, Yunika (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2024)
Mango fruit that is consumed daily has several benefits such as increasing the body’s immunity, facilitating digestion, supporting eye health, helping hair and skin health, helping reduce cancerrisk, emphasizing cholesterol levels, and nourishing the heart. Mango post-harvest handling is a critical activity that needs attention before mango fruit reaches consumers. Mango fruit storageis closely related to distribution and marketing activities. This study aims to determine how to store at different temperatures for seven days. This study used the storage temperature treatment of arum manis mango. The treatments used were 5-10oC, 15-20oC, 27-32oC, and 35-40oC. The main parameters were vitamin C levels in each treatment and a decrease in vitamin C levelsduring storage. Storage at a temperature of 5-10oC produces an average vitamin C content of 6.84 ± 0.28 mg/ 100 g. Storage at room temperature (27-32oC) resulted in an average vitamin Ccontent of 3.91 ± 0.44 mg/ 100 g. The vitamin C content of the freshly harvested sweet arum mango fruit was 7.53 ± 0.40 mg/ 100 g. Storage at low temperatures is the best choice tomaintain the quality of vitamin C of arum manis mango.